1994
DOI: 10.1111/j.1540-8159.1994.tb02463.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Serotonin Reuptake Inhibitors for the Treatment of Recurrent Syncope Due to Carotid Sinus Hypersensitivity Unresponsive to Dual Chamber Cardiac Pacing

Abstract: Carotid sinus hypersensitivity can be a cause of recurrent unexplained syncope in the older patient. Dual chamber cardiac pacing may relieve the bradycardia, but may not affect the vasodilatory component of this disorder. We report on two patients with carotid sinus hypersensitivity with a predominant vasodilatory component who experienced recurrent syncope following permanent pacemaker implantation. Both patients were treated with serotonin reuptake inhibitors and after 4-6 weeks of therapy had complete resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…For the most part, dualchamber cardiac pacing is preferred (level B) [306][307][308] , although it has been argued that single-chamber ventricular pacing may be sufficient in those relatively infrequent cases in which there is absence of both a marked vasodepressor component to the hypotension and so-called 'ventricular pacing effect' [71] . Medical therapy for carotid sinus syndrome has largely been abandoned [310,311] . There are as yet no randomized studies examining treatment of carotid sinus syncope in which hypotension is predominantly of vasodepressor origin.…”
Section: Carotid Sinus Syndromementioning
confidence: 99%
“…For the most part, dualchamber cardiac pacing is preferred (level B) [306][307][308] , although it has been argued that single-chamber ventricular pacing may be sufficient in those relatively infrequent cases in which there is absence of both a marked vasodepressor component to the hypotension and so-called 'ventricular pacing effect' [71] . Medical therapy for carotid sinus syndrome has largely been abandoned [310,311] . There are as yet no randomized studies examining treatment of carotid sinus syncope in which hypotension is predominantly of vasodepressor origin.…”
Section: Carotid Sinus Syndromementioning
confidence: 99%
“…17 Accordingly, the role of this neurotransmitter in cardiovascular disorders that involve neurally mediated hypotension and bradycardia has received great interest. In particular, SSRIs have been used as a therapy in chronic orthostatic hypotension, 6 carotid sinus hypersensitivity, 7,18 and NMS. 19 Grubb et al 6 evaluated the usefulness of fluoxetine hydrochloride, a selective SSRI, in 16 patients with recurrent syncope and a positive tilt-table test.…”
Section: Previous Animal Studiesmentioning
confidence: 99%
“…On the basis of these animal studies, several investigators have examined the usefulness of serotonin reuptake inhibitors as a therapy for neurally mediated cardiovascular disorders. [5][6][7]16 The Role of SSRIs in Neurally Mediated Cardiovascular Disorders…”
Section: Previous Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In carotid sinus syndrome, Grubb et al 40 observed apparently beneficial effects of sertraline in one case and fluoxetine in another. These observations, if confirmed, may be important because, with the possible exception of midodrine, there are as yet no other pharmacological agents to assist in treating patients with nonvasovagal neurally mediated syncope.…”
Section: Serotonin Reuptake Blockersmentioning
confidence: 99%